Islam & Natural Philosophy: Principles of Daqīq Al-Kalām (Basil Altaie) - Al Asyari, Hasan; Arrozy, Juris (Universitas Islam Internasional Indonesia, 2024)
Islam & Natural Philosophy: Principles of Daqīq Al-Kalām (Basil Altaie). Oldham: Beacon Books, 2023. The discipline of kalām (Islamic rational theology) can be generally divided into two categories: jalīl al-kalām and daqīq al-kalām. The former mainly deals with theological questions whereas the latter deals with questions related to natural philosophy such as causality, free will, time, space, etc. The book under review deals with the latter: it provides an original attempt to revive and recontextualize daqīq al-kalām. Trained as a theoretical physicist in Mosul, Iraq, and Manchester, the United Kingdom, with some 30 years of exposure to the field of kalām, the Iraqi author offers an interesting interplay between classical Islamic theology and modern scientific discoveries.